The metabolic underpinning of eating disorders: A systematic review and meta-analysis of insulin sensitivity. (1st November 2019) - Ilyas, Athif; Hübel, Christopher; Stahl, Daniel; Stadler, Marietta; Ismail, Khalida; Breen, Gerome; Treasure, Janet; Kan, Carol
Abstract: Background: A recent study reported a positive genetic correlation between anorexia nervosa and insulin sensitivity using data from genome-wide association studies. Epidemiological studies have, on the other hand, suggested that bulimia nervosa and binge-eating disorder are associated with decreased insulin sensitivity. The aim of this study was to conduct a systematic review and meta-analysis of insulin sensitivity across the spectrum of eating disorders. Methods: EMBASE, Medline, and PsycINFO were searched for all relevant studies published until January 2017, and retrieved studies were assessed for eligibility by two independent reviewers as per predefined inclusion criteria. The associations between eating disorder subtypes and insulin sensitivity were analysed separately. Individual effect sizes were standardized, and a meta-analysis was performed to calculate a pooled effect size using random effects. Results: Of 296 citations retrieved, 22 studies met the inclusion criteria, and 12 studies had appropriate data for meta-analysis. Using the random effects model, the pooled effect size (95% confidence interval) was 1.66 (0.79, 2.54) in people with anorexia nervosa ( n  = 340) and −0.57 (−0.80, −0.34) in people with bulimia nervosa ( n  = 120) and binge-eating disorders ( n  = 3241). Interpretation: Anorexia nervosa is associated with increased insulin sensitivity whilst bulimia nervosa and binge-eating disorders are associated with decreased insulin sensitivity. The possible mechanism underpinning these findings needs to be determined.